Topical Kombucha as a Natural Antioxidant Against Skin Photoaging: A Literature Review - Milka Ivenna Soeyanto; I Made Muliarta (Green Publisher Indonesia, 2025)
Skin photoaging refers to degenerative changes in the skin primarily triggered by chronic exposure to ultraviolet (UV) radiation, especially UV-B. This exposure leads to the formation of reactive oxygen species (ROS), stimulates inflammatory responses, and accelerates collagen breakdown through the activation of matrix metalloproteinases (MMPs). These processes affect the extracellular matrix and skin homeostasis, and contribute to visible signs such as wrinkles, skin dryness, and loss of elasticity. Natural antioxidants in topical formulations have gained attention for their protective effects. Kombucha, a fermented tea rich in polyphenols, organic acids, and flavonoids has shown potential in reducing MMP-1 expression, enhancing TGF-β signaling, and stimulating collagen production. When fermented with Hibiscus sabdariffa (rosella), its antioxidant activity is further enhanced. This review highlights the molecular mechanism of photoaging and highlights the therapeutic potential of Kombucha Roella as a natural topical agent. Despite promising results, further in vivo and clinical studies are needed to confirm its efficacy.